2020
DOI: 10.1111/1756-185x.13897
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and associated factors in a multi‐ethnic cohort of rheumatoid arthritis patients

Abstract: Introduction: Fatigue is an important yet infrequently evaluated component in patients with rheumatoid arthritis (RA) and may have a major impact on quality of life. Objectives: To evaluate fatigue, identify factors associated with fatigue and assess the effect of fatigue on health-related quality of life (HRQoL) in a multi-ethnic cohort of RA patients. Methods: A cross-sectional study was performed in patients who fulfilled European League Against Rheumatism/ American College of Rheumatology 2010 criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Madsen et al [ 29 ], Lao et al [ 16 ], Bingham et al [ 30 ], Abdel-Magied et al [ 17 ], Olsen et al [ 27 ], Holdren et al [ 31 ], and Bączyk and co-authors [ 24 ], confirming that increased pain and its changing nature increased fatigue levels. Lee et al [ 22 ], Hammam et al [ 15 ], and Wagan et al [ 18 ] analyzed the influence of hemoglobin concentration on fatigue; their studies did not show a relationship between the variables, in contrast to the results of our studies. On the other hand, the influence of low hemoglobin values on fatigue was confirmed by Madsen et al [ 29 ], van Steenbergen et al [ 25 ], and Olsen et al [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Madsen et al [ 29 ], Lao et al [ 16 ], Bingham et al [ 30 ], Abdel-Magied et al [ 17 ], Olsen et al [ 27 ], Holdren et al [ 31 ], and Bączyk and co-authors [ 24 ], confirming that increased pain and its changing nature increased fatigue levels. Lee et al [ 22 ], Hammam et al [ 15 ], and Wagan et al [ 18 ] analyzed the influence of hemoglobin concentration on fatigue; their studies did not show a relationship between the variables, in contrast to the results of our studies. On the other hand, the influence of low hemoglobin values on fatigue was confirmed by Madsen et al [ 29 ], van Steenbergen et al [ 25 ], and Olsen et al [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Uhlig and Provan [ 19 ], Feldthusen et al [ 20 ], and Katz et al [ 21 ] also indicated that factors such as age and gender were not significantly associated with fatigue. Different results can be seen in the studies by Lee et al [ 22 ] and Diniz et al [ 23 ]. These studies showed that younger age is significantly associated with higher fatigue values, but gender is not.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Fatigue, arthritis, and deformity are the main complications of RA, which lead to the impairment of body function (Englbrecht et al, 2013). Studies from different countries and regions show that fatigue is highly prevalent in patients with RA (40%-80%) (Lee et al, 2020). The most common symptom is pain (Borenstein et al, 2010), which has a negative impact on body function and quality of life (Boyden et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, higher HAQ-DI score (>1.0) indicates the patient has moderate to severe functional disabilities and could predict worse outcomes. 35,36 Both procedures in our study were performed in older adults with relatively low ADL. It is reasonable to presume that toe arthroplasty alone resulted in only limited improvement in SAFE-Q subscale scores.…”
Section: Discussionmentioning
confidence: 99%